Pengaruh Media Pembelajaran Digital Terhadap Motivasi dan Hasil Belajar IPAS - Khaulah Afifa; Tri Astuti (Jurnal Penelitian Pendidikan IPA, 2024)
This research is a quantitative research conducted in class V SD Gugus Wijaya Kusuma. The purpose of this study was to determine the effect of Digital Learning Media on the Moivation and Learning Outcomes of students in IPAS lessons in class V. In this study researchers focused on social studies subjects. In the study, three variables were analyzed, namely two independent variables and one dependent variable. Pupulations and samples of this study were 59 students. Data collection techniques through interview techniques, observation and questionnaire distribution and also secondary data. Data analysis in this study was carried out by testing validity, reliability, classical assumptions, and hypotheses. In testing the hypothesis of this study conducted by means of t test to get the influence between variables X1 to Y, X2 to Y. The results of the research that has been done found that, from the results of the t test coefficients of media on motivation, the significance value is 0.000 <0.05, meaning that there is an influence of media on learning motivation. From the results of the t test Constant media on motivation obtained R Square value of 0.452 means that the media variable affects student learning motivation by 45.2% and the rest is influenced by other factors. From the results of the t test media coefficients on the results of a significance value of 0.000 <0.05 means that there is an influence of the media on learning outcomes. From the results of the t test Constant media on the results obtained R Square value of 0.202. This means that the media variable affects student learning outcomes by 20.2% and the rest is influenced by other factors. Based on the results of data analysis, it means that digital learning media has an effect on the motivation and learning outcomes of fifth grade students in social studies lessons in Wijaya Kusuma Gugus.